Structure-Activity Relationships Among a Group of 7-[α-(N, N′-Substituted-Amidinothio)-Acetamido] Cephalosporanic Acids - Misiek, M. (1972)
Structure-activity relationships were examined for a number of 7-[α-(N,N′-substituted-amidinothio)-acetamido] cephalosporanic acids, including several wherein the amidino group was cyclized into six, seven, and eight-membered rings and a series wherein alkyl, cycloalkyl, alkenyl, and alkynyl radicals were substituted on the nitrogens of the noncyclized amidino group. Derivatives containing an unsubstituted cyclized amidino group had comparable antibacterial activity in vitro and in general had a spectrum of activity broader than that of cephalothin, especially against cephalothin-resistant strains of Escherichia, Klebsiella, and Proteus. When administered parenterally, the cephalosporin with the six-membered cyclized amidino group was as effective as cephalothin in experimental infections of mice produced by cephalothin-sensitive gram-negative organisms and more efficacious in infections caused by cephalothin-resistant strains. Among the cephalosporins with noncyclized amidino groups, those with an ethyl substituent on one of the nitrogens and a C(2)-C(4) alkyl radical, particularly propyl on the other, were the most active. They not only had a better profile of activity in vitro than cephalothin and the cephalosporin derivatives having a cyclized amidino group, but were also more efficacious in infections of mice.